The Gender Contract under Neoliberalism: Palestinian-Israeli Women's Labor Force Participation. - Sa'ar, Amalia (Feminist Economics, 2017)
This paper interprets the pressure to raise Palestinian-Israeli women’s labor force participation within the unfolding neoliberal project in Israel, arguing that women’s stalled workforce integration reflects embedded economic rationality. Poor infrastructure and discriminatory policies, combined with Israel’s rapid economic privatization, set contradictory expectations for Palestinian-Israeli women: their opportunity-cost calculations include entitlements to economic protection alongside obligations to provide expenditure-saving domestic labor. Yet growing pressure and desire to join the paid workforce suggest that the gender contract may be changing. This cultural schema, which links women’s economic strategizing to their sense of feminine propriety, is transforming as part of a broader transition to a market-led gender regime, with the paradoxical effect of encouraging women’s employment while simultaneously impoverishing them. By dwelling on the dialectics of culture and the structure of work opportunities, and women’s agency, this paper aims to resolves an impasse in the current debate on women’s low workforce participation.